2016
DOI: 10.1021/acs.jpcc.6b09315
|View full text |Cite
|
Sign up to set email alerts
|

Hiding the Headgroup? Remarkable Similarity in Alkyl Coverage of the Surfaces of Pyrrolidinium- and Imidazolium-Based Ionic Liquids

Abstract: The liquid–vacuum interfaces of a series of ionic liquids (ILs) containing 1-alkyl-1-methylpyrrolidinium ([C n mpyrr]+) cations of different alkyl chain lengths have been studied by reactive-atom scattering with laser-induced fluorescence detection (RAS-LIF) and molecular dynamics (MD) simulations. A direct, quantitative comparison has been performed between [C n mpyrr]+ and the previously better-characterized 1-alkyl-3-methylimidazolium ([C n mim]+) ILs with the same chain lengths, n, and common anion, bis­(t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…49 − 51 , 54 , 56 We have shown the power of the RAS-LIF and RAS-MS methods to analyze the extreme outer surfaces of a number of IL systems, including homologous series of imidazolium- and pyrrolidinium-based liquids, the coupled effects of variation of the anion, and even liquid-crystalline materials. 47 53 The majority of this work has used ground-state oxygen, O( 3 P), atoms as the projectile, with the detection of OH (RAS-LIF) or inelastically scattered O, OH, and H 2 O (RAS-MS). Recently, we have also shown that RAS-MS can be extended to F( 2 P) projectiles, combined with the detection of HF, or DF for isotopically labeled samples, giving detailed site-specific information on the occupancy and orientation of cations at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…49 − 51 , 54 , 56 We have shown the power of the RAS-LIF and RAS-MS methods to analyze the extreme outer surfaces of a number of IL systems, including homologous series of imidazolium- and pyrrolidinium-based liquids, the coupled effects of variation of the anion, and even liquid-crystalline materials. 47 53 The majority of this work has used ground-state oxygen, O( 3 P), atoms as the projectile, with the detection of OH (RAS-LIF) or inelastically scattered O, OH, and H 2 O (RAS-MS). Recently, we have also shown that RAS-MS can be extended to F( 2 P) projectiles, combined with the detection of HF, or DF for isotopically labeled samples, giving detailed site-specific information on the occupancy and orientation of cations at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of pyrrolidinium-based ILs with C nmim + -based ILs found the similarity of the two kinds of cations in the dependence of the surface structure on the alkyl chain length. 42,63,64 In the nonpolar region at the surface, alkyl chains are not fully packed. Hence, other parts of IL ions, such as polar parts of the cation and the polar/nonpolar parts of the anion, are also exposed at the surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Experiments capable of quantifying the relative populations of preferred ion conformations are crucial to the development and verification of realistic models of the liquid–vacuum interface of RTILs and other molecular liquids. Methods like sum-frequency generation (SFG) and angle-resolved X-ray photoelectron spectroscopy (ARXPS) have made important contributions to our understanding of the average orientation of specific ions at the liquid–vacuum interface of common RTILs. A smaller number of studies using molecular dynamics (MD) simulations and low-energy ion scattering (LEIS) have addressed the distribution or relative populations of ion conformations at such interfaces. Our own investigations of the RTIL–vacuum interface with the use of reactive-atom scattering have revealed general features of the interface through signatures in the scattering dynamics. Unlike studies of inelastic scattering on interfaces with noble gas atoms, reactive-atom scattering is intrinsically chemically specific because the scattered reaction product carries an interfacial atom that the probe atom must have come into contact with before the product exited the interface. Thus, the resulting reactive-atom scattering signals sum over all sites that expose the interfacial atom to the probe atom.…”
mentioning
confidence: 99%